Research Trends On Mathematical Reasoning: A Systematic Literature Review - Sari, Intan Kartika; Putra, Zetra Hainul; Witri, Gustimal; Noviana, Eddy; Kurniaman, Otang; Mulyani, Eva Astuti; Permana, Dede (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
Mathematical reasoning is essential for understanding mathematics. This literature study determines the development of learners’ mathematical reasoning abilities over the last 3 years. This study presents a literature review regarding the development of mathematical reasoning, including media, strategies, and measurement instruments, to serve as a basis for future mathematical reasoning research. The literature study method used is a systematic literature review (SLR), using a review procedure that refers to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework in the period 2021 to 2023 because the development of mathematical reasoning literature studies is very significant and recent. Data collection was performed by reviewing 20 Scopus-indexed articles from the Scopus database. The results of the research reveal that from the 20 selected pieces of literature, it can be interpreted that mathematical reasoning abilities can be improved and fulfill the indicators of mathematical reasoning itself by providing innovative media, strategies, and instruments in mathematics learning. The innovation provided can be in the form of technology integration (Geogebra), strategies that are no longer conventional, and the reasoning indicator instrument itself. Thus, students’ mathematical reasoning abilities are no longer included in the low category in solving mathematical problems.